Powered by www.myengg.

com

INDEFINITE INTEGRATION
PREVIOUS EAMCET BITS 1.

∫ ( x + 1)
Ans:

dx 4x + 3

[EAMCET 2009]

1) tan −1 4x + 3 + c 2) 3 tan −1 4x + 3 + c

3) 2 tan −1 4x + 3 + c
1 tdt =∫ 2 2 ⎛ t −3 ⎞ + 1⎟ t ⎜ ⎝ 4 ⎠

4) 4 tan −1 4x + 3 + c

Sol: 4x + 3 = t 2

t2 − 3 x= 4

4dx = 2tdt

=∫

2 dt = 2 tan −1 t + c = 2 tan −1 t +t
2

(

4x + 3 + c

)

dx = 2.

1 tdt 2
x

∫ ⎜ 1 − cos 2x ⎟ e dx ⎝ ⎠
1) −e x cot x + c Ans: 1 2) e x cot x + c 3) 2e x cot x + c

⎛ 2 − sin 2x ⎞

[EAMCET 2009]
4) −2e x cot x + c

Sol:

∫⎜ ⎝

⎛ 2 − 2sin x cos x ⎞ x 2 x ⎟ e dx = ∫ ( cos ec x − cot x ) e dx 2 2sin x ⎠

= ∫ e x ⎡( − cot x ) + cos ec 2 x ⎤ dx ⎣ ⎦
e x ( − cot x ) + c ⎡∵ ∫ e x ⎡f ( x ) + f ′ ( x ) ⎤ dx = e x f ( x ) + c ⎤ ⎣ ⎦ ⎣ ⎦ 3. If I n = ∫ sin n xdx then nI n − ( n − 1) I n − 2 =
1) sin n −1 x cos x
Ans: 1 sin n −1 x sin x Sol: I n = ∫ dx u v 2) cos n −1 x sin x 3) – sin n −1 x cos x

[EAMCET 2009]
4) − cos n −1 x sin x

I n = sin n −1 x ( − cos x ) − ∫ ( n − 1)( sin x )
I n = − sin n −1 x cos x + ( n − 1) ∫ ( sin x )

n −2

( cos x )( − cos x ) dx
2

n −2

(1 − sin x ) dx

I n = − sin n −1 x cos x + ( n − 1) ∫ sin n − 2 xdx − ( n − 1) ∫ sin n xdx
I n = − sin n −1 x cos x + ( n − 1) I n − 2 − ( n − 1) I n ⇒ nI n − ( n − 1) I n − 2 = sin n −1 x cos x

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration
4. ⎛ 1 − sin x ⎞ If ∫ e x ⎜ ⎟ dx = f ( x ) + c then f (x) = ⎝ 1 − cos x ⎠ ⎛x⎞ 1) e x cot ⎜ ⎟ ⎝2⎠ Ans:3 ⎛x⎞ 2) e − x cot ⎜ ⎟ ⎝2⎠ ⎛x⎞ 3) −e x cot ⎜ ⎟ ⎝2⎠

[EAMCET 2008]
⎛x⎞ 4) −e − x cot ⎜ ⎟ ⎝2⎠

x x⎞ ⎛ ⎜ 1 − 2sin 2 cos 2 ⎟ x⎤ x ⎡1 2 x Sol: ∫ e x ⎜ ⎟dx = ∫ e ⎢ cos ec − cot ⎥ dx x 2 2⎦ ⎣2 ⎜ ⎟ 2sin 2 2 ⎝ ⎠ x⎞ ⎛ ⎡ = e x ⎜ − cot ⎟ + c ⎣∵ ∫ e x ⎡ f ( x ) + f ′ ( x ) ⎤dx = e x f ( x ) + c ⎤ ⎣ ⎦ ⎦ 2⎠ ⎝

∴f ( x ) = −e x cot

x 2
[EAMCET 2008]
4) x n + ecx

5.

If I n = ∫ x n ecx dx for n ≥ 1 then c.I n + n.I n −1 = 1) x n ecx Ans: 1 x n ecx . dx u v
⎞ ⎟dx ⎠

2) x n

3) ecx

Sol: I n = ∫

⎛ e cx x n ∫ ecx dx − ∫ n.x n −1. ⎜ ⎝ c
n

⎛ ecx ⎞ n n cx In = x ⎜ ⎟ − I n −1 ⇒ CI n = x e − nI n −1 ⎝ c ⎠ c C.I n + nI n −1 = x n ecx 6. If ∫ e x (1 + x ) .sec 2 ( xe x ) dx = f ( x ) + c then f ( x ) = 1) cos ( xe x ) Ans: Sol: Let xe x = t 2) sin ( xe x ) 3) 2 tan −1 x
[EAMCET 2008]

4) tan ( xe x )
2 x 2

( x.e
7. I∫

x

+ e x .1) dx = dt

∫ e ( x + 1) sec ( xe ) dx = ∫ sec = tan t + c ⇒ tan ( xe ) + c
x x

tan

e x ( x + 1) dx = dt

∴f ( x ) = tan ( xe x )
[EAMCET 2007]

ex − 1 dx = f ( x ) + c then f(x) is equal to ex + 1

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration
1) 2 log ( e x + 1)
Ans: 3 2e x − ( e x + 1) ex + ex − ex − 1 Sol: = ∫ dx ⇒ ∫ dx ex + 1 ex + 1 =∫ 2e x ex + 1 ex dx − ∫ x dx = 2 ∫ x dx − ∫ 1dx ex + 1 e +1 e +1 2) log ( e 2x − 1) 3) 2 log ( e x + 1) − x 4) log ( e 2x + 1)

= 2 log e x + 1 − x + c
∴ f ( x ) = 2 log ( e x + 1) − x 8.

∫ tan
1)

−1

⎛ 1− x ⎜ ⎜ 1+ x ⎝

⎞ ⎟ dx = ⎟ ⎠

[EAMCET 2007]

( 1 3) ( x sin 2
Ans: =

1 x cos −1 x − 1 − x 2 + c 2
−1

x−

) 1− x ) + c
2

2) 4)

1 x cos −1 x + 1 − x 2 + c 2
−1

( 1 ( x sin 2

x+

) 1− x ) + c
2

Sol: Put x = cos2θ ⎛ 1 − cos 2θ ⎞ tan −1 ⎜ ∫ ⎜ 1 + cos 2θ ⎟ dx ⎟ ⎝ ⎠ = = = = ⎤ −1 1 ⎡ −1 .xdx ⎥ ⎢cos x.x − ∫ 2⎣ 1− x2 ⎦ ⎤ −2x 1 ⎡ −1 1 dx ⎥ ⎢cos x.x − ∫ 2⎣ 2 1− x2 ⎦ 1 ⎡ −1 1 2⎤ ⎢cos x.x − 2 × 2 1 − x ⎥ + c 2⎣ ⎦ 1 ⎡ −1 cos x.x − 1 − x 2 ⎤ + c ⎣ ⎦ 2
[EAMCET 2007]

=

∫ tan

−1

(

tan θ dx
2

)

= ∫ θdx = = 9.

∫ 2 cos

1

−1

xdx

1 −1 ∫ c os x.1.dx 2

∫ 4sin x + 6 cos x dx
1 1) x + log 4sin x + 6 cos x + c 2 3) x + 2 log 2sin x + 3cos x + c Ans: 1 2) 2x + log 2sin x + 3cos x + c 4)

sin x + 8cos x

1 log 4sin x + 6 cos x + c 2

Sol:

∫ c cos x + d sin x dx = ⎜ c ⎝

a cos x + b sin x

⎛ ac + bd ⎞ ⎛ ad − bc ⎞ x +⎜ 2 log ( cos x + d sin x ) + c 2 2 ⎟ 2 ⎟ +d ⎠ ⎝ c +d ⎠

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

∫ 6 cos x + 4sin x dx = ⎜ 36 + 16 ⎟ x + ⎜ 36 + 16 ⎟ log 6 cos x + 4sin x + c ⎝ ⎠ ⎝ ⎠
1 = x + log 6 cos x + 4sin x + c 2
10. If

8cos x + 1.sin x

⎛ 48 + 4 ⎞

⎛ 32 − 6 ⎞

x dx = g ( x ) + c then g(x) is equal to a − x3
3

[EAMCET 2006]
2 ⎛x⎞ co s −1 ⎜ ⎟ 3 ⎝a⎠

1)

2 cos −1 x 3

2)

2 −1 ⎛ x 3 ⎞ sin ⎜ 3 ⎟ 3 ⎝a ⎠

3)

2 −1 ⎛ x 3 ⎞ sin ⎜ 3 ⎟ ⎜ a ⎟ 3 ⎝ ⎠

4)

Ans: Sol:

x ⎛ x ⎞ a 3 ⎜1 − 3 ⎟ ⎝ a ⎠
3

dx =

1 a∫

x/a ⎛x⎞ 1− ⎜ ⎟ ⎝a⎠
3

dx

Let

x = sin 2 / 3 θ a

1 ( sin θ ) 2a cos θ = ∫ × × dθ 2 a 1 − sin θ 3 ( sin θ )1/ 3
1/ 3

dx = a.
dx =

2 2 −1 ( sin θ ) 3 cos θdθ 3

=

2 2 ∫ 1.dθ ⇒ 3 θ + c 3

2a cos θ dθ × 3 ( sin θ )1/ 3

⎛ x3 ⎞ 2 = sin −1 ⎜ 3 ⎟ + c ⎜ a ⎟ 3 ⎝ ⎠ ⎛ x3 ⎞ 2 ∴ g ( x ) = sin −1 ⎜ 3 ⎟ + c ⎜ a ⎟ 3 ⎝ ⎠ 11. If

∫x

2

dx = f ( x ) + c then f(x) is equal to + 2x + 2 2) 2 tan −1 ( x + 1) 3) − tan −1 ( x + 1)

[EAMCET 2006]

1) tan −1 ( x + 1) Ans: 1 Sol:
dx
2

4) 3 tan −1 ( x + 1)

∫ ( x + 1)

+1

= tan −1 ( x + 1) c

∴ f ( x ) = tan −1 ( x + 1) 12. Observe the following statements :
x −1 ⎛ x 2 + 1 ⎞ x −1 A : ∫ ⎜ 2 ⎟ e x dx = e x + c ⎝ x ⎠
2 2

[EAMCET 2006]

R : ∫ f 1 ( x ) .ef (x ) dx = f ( x ) + c , then which of the following is true ? 1) Both A and R are true and R is the correct reason of A

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration
2) Both A and R are true and R is the correct reason of A 3) A is true, R is false Ans: 3 Sol: R :
1 f (x ) ∫ f ( x ) .e dx

4) A is false, R is true 1 ⎞ ⎜ x− ⎟ ⎛ A : ∫ ⎜1 + 2 ⎟ e⎝ x ⎠ dx ⎝ x ⎠ Let x −
⎛ 1⎞

Let f(x) = t

1 =t x

∫ f ( x ) dn = dt
1 t t ∫ e dt = e + c

1 ⎞ ⎛ ⎜1 + 2 ⎟ dx = dt ⎝ x ⎠
t t ∫ e dt = e + c = e
x 2 −1 x

x−

1 x

+c

=e

f (x )

+c

=e

+c

Here A is true and R is false 13. If

∫ cos x (1 + cos x ) dx = f ( x ) + c
1 + cos x cos x 2) log c os x 1 + cos x 3) log sinx 1 + sin x 4) log

sin x

[EAMCET 2005]
1 + sinx sin x

1) log Ans: 1

Sol: Let cosx = t – sinxdx = dt

∫ t (1 + t ) = ∫ ⎜ ⎝
= log

−dt

⎛ −1 1 ⎞ + ⎟ dt t t +1⎠

= − log t + log | t + 1| +c t +1 1 + cos x + c = log +c t cos x 1 + cos x +c cos x dx = K ⎡ tan −1 ( x 50 ) ⎤ + c , then K = ⎣ ⎦
2

∴ f ( x ) = log

14.


1)

x 49 tan −1 ( x 50 ) 1 + x100 1 50

[EAMCET 2005]
4) − 1 100

2) −

1 50

3)

1 100

Ans: Sol: Let tan −1 ( x 50 ) = t

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration
1+ (x = 15. 1
50 2

)

× 50.x 49 dx = dt
2 dt 1 t2 1 ⎡ tan −1 50 ⎤ + c = × +c ⇒ ⎣ ⎦ 50 50 2 100

x 49 dx dt = = 100 1+ x 50

∫t

⎛ 2x ⎞ 2 If ∫ sin −1 ⎜ ⎟ dx = f ( x ) − log 1 + x + c then f(x) = 1+ x2 ⎠ ⎝ 1) 2x tan −1 x Ans: 1 2) −2x tan −1 x 3) x tan −1 x

[EAMCET 2005]
4) – x tan −1 x

Sol:

∫ sin

−1

⎛ 2x ⎞ −1 ⎜ ⎟ dx = ∫ 2 tan xdx 1+ x2 ⎠ ⎝ = 2 ∫ tan −1 x.1.dx 1 ⎡ ⎤ = 2 ⎢ tan −1 x.∫ 1.dx − ∫ .xdx ⎥ 2 1+ x ⎣ ⎦ = 2x tan −1 x − log 1 + x 2 + c ∴f ( x ) = 2x tan −1 x

16.

∫ ( x + 100 )
Ans: 3

dx x + 99
1/ 2

= f (x) + c ⇒ f (x) = 2) 3 ( x + 100 )
1/ 2

[EAMCET 2004]
3) 2 tan −1

1) 2 ( x + 100 )

(

x + 99

)

4) 2 tan −1

(

x + 100

)

Sol: Let x + 99 = t2 dx = 2t dt x + 100 = ( x + 99 ) + 1 ⇒ t 2 + 1

∫ ( x + 100 )
= 2 tan −1

dx x + 99

=∫

2tdt = 2 tan −1 ( t ) + c ( t + 1) t
2

(

x + 99 + c

)

∴ f ( x ) = 2 tan −1 17.

(

x + 99

)
[EAMCET 2004]
3) 1+ x x −1 4) x −1 1+ x

3 − x2 x x ∫ 1 − 2x + x 2 .e dx = e f ( x ) + c ⇒ f ( x ) = 1) 1+ x 1− x 2) 1− x 1+ x

Ans:1

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration
Sol: = − ∫ x2 − 3

( x − 1)

2

.e dx ⇒ − ∫
x

(x

2

− 1) − 2
2

( x − 1)

e x dx

⎡ ( x + 1)( x − 1) 2 ⎤ x = −∫ ⎢ − e dx 4 2 2⎥ ( x − 1) ⎥ ⎢ ( x − 1) ⎣ ⎦ ⎡ x +1 2 ⎤ x ⎡ x + 1⎤ = ∫⎢ − +c .e .dx ⇒ −e x ⎢ 2⎥ ⎣ x − 1⎥ ⎦ ⎢ x − 1 ( x + 1) ⎥ ⎣ ⎦ 1+ x ⎛ x +1⎞ = ex ⎜ ⎟ + c ⇒ f (x) = 1− x ⎝ 1− x ⎠ 18.

∫ sin x cos x dx = −f ( x ) + c ⇒ f ( x ) =
1) 2 tan x Ans: 4 2) – 2 tan x 3) – 2 cot x

cot x

[EAMCET 2004]
4) 2 cot x

cot x cos ec 2 x cot x.cos ec2 x Sol: ∫ × dx = ∫ dx sin x cos x cos ec 2 x cot x = −∫ cos ec 2 x dx = −2 cot x + c cot x

∴ f ( x ) = 2 cot x 19. 1+ x + x + x2 ∫ x + 1 + x dx = 1) 1 1+ x + c 2 2) 2 3/ 2 (1 + x ) + c 3 3) 1 + x + c 4) 2 (1 + x )

[EAMCET 2003]
3/ 2

+c

Ans: Sol: =

(

1+ x

)

2

+ x. 1 + x dx

x + 1+ x

=∫
= 20.

1+ x ⎡ 1+ x + x ⎤ ⎣ ⎦ dx x + 1+ x
1 + x dx =
−1

2 (1 + x ) 3
dx =

3/ 2

+c

∫ (1 + x − x ) e
−1

x + x −1

[EAMCET 2003]
−1

1) (1 + x ) e x + x + c 2) ( x − 1) e x + x + c Ans:

3) − xe x + x + c

−1

4) xe x + x + c

−1

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration
1 1 1 x+ ⎤ ⎡⎛ 1 ⎞ x + x ⎛ 1 ⎞ x+ x x Sol: ∫ ⎜1 − + x ⎟e dx = ∫ ⎢⎜ 1 − ⎟ e + xe ⎥dx ⎝ x ⎠ ⎣⎝ x ⎠ ⎦ x+ 1 x

Let xe

=t

⎡ x+ 1 ⎛ 1 ⎞ x+ 1 ⎤ x.e x ⎜ 1 − 2 ⎟ + e x ⎥ dx = dt ⎢ ⎝ x ⎠ ⎣ ⎦

e

x+

1 x

1 ⎞ ⎛ ⎜ x − + 1⎟ dx = dt x ⎠ ⎝

= ∫ 1.dt = t + c xe 21.
x+ 1 x

+c

∫ 1 − cos x − sin x =
1) log 1 + cot Ans: 3

dx

[EAMCET 2002]
3) log 1 − cot

x x + c 2) log 1 − tan + c 2 2

x +c 2

4) log 1 + tan

x +c 2

Sol:

∫ 1 − cos x − sin x
=∫ dx = 2sin x / 2 − 2sin x / 2 cos x / 2 ∫
2

dx

dx x⎡ x⎤ 2sin 2 ⎢1 − cot ⎥ 2⎣ 2⎦

1 x cos ec 2 dx x 2 =∫2 = log 1 − cot + c x 2 1 − cot 2 22.

∫ 7 + 5cos x =
1) 3) 1 x⎞ ⎛ 1 tan −1 ⎜ tan ⎟ + c 2⎠ 3 ⎝ 3 1 x⎞ ⎛ tan −1 ⎜ tan ⎟ + c 7 2⎠ ⎝ dx 2) 4) 1 x⎞ ⎛ 1 tan −1 ⎜ tan ⎟ + c 2⎠ 6 ⎝ 6 1 x⎞ ⎛ tan −1 ⎜ tan ⎟ + c 4 2⎠ ⎝

dx

[EAMCET 2002]

Ans: 2 Sol:

∫ 7 + 5cos x

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

x 2 use cos x = x 1 + tan 2 2 1 − tan 2 x sec 2 . dx 1 2 = ∫ ∫ x 2 12 + 2 tan 2 2 Put tanx/2 = t = 23. 1 x⎞ ⎛ 1 tan −1 ⎜ tan ⎟ + C 2⎠ 6 ⎝ 6 3x 9x − 1 dx = 2) 4)
[EAMCET 2002]

sec2

( 6)

x dx 2 x 2

2

+ tan 2


1) 3)

1 log 3x + 9 x − 1 + c log 3
1 log 3x − 9x − 1 + c log 9 3x 9x − 1

1 log 3x − 9 x − 1 + c log 3
1 log 9x + 9 x − 1 + c log 3

Ans: 1 Sol:

dx

3x = t ⇒ 3x log 3dx = dt 1 dt 1 x x ∫ t 2 − 1 = ( log 3) log 3 + 9 − 1 + C log 3 24.


1)

dx = x ( x + 9) 2 tan −1 3

[EAMCET 2001]
−1

( x ) + C 2) 2 tan 3

⎛ x⎞ ⎜ ⎜ 3 ⎟+C ⎟ ⎝ ⎠

3) tan −1

( x)+C

⎛ x⎞ 4) tan −1 ⎜ ⎜ 3 ⎟+C ⎟ ⎝ ⎠

Ans: 2 Sol:

dx x ( x + 9) dx = 2tdt 2tdt t ( t 2 + 9) dt 2 ⎛t⎞ = tan −1 ⎜ ⎟ + C 2 t +3 3 ⎝3⎠
2

Let x = t2 , ⇒∫ = 2∫

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

= 25.

⎛ x⎞ 2 tan −1 ⎜ ⎜ 3 ⎟+C ⎟ 3 ⎝ ⎠
2

∫ ( x + 1)
Ans: 4

e x dx = 2) x 2 e x + c 3) ( x + 1) e x + c

[EAMCET 2001]

1) xe x + c

4) ( x 2 + 1) e x + c

Sol:

∫ ( x + 1) e dx ∫ ( x + 1 + 2x ) .e dx
2 x 2 x

Let f ( x ) = x 2 + 1 ⇒ f ′ ( x ) = 2x

⎣ ⎦ ∫ ⎡f ( x ) + f ′ ( x )⎤ e dx = f ( x ) .e
x

x

+c

= ( x 2 + 1) e x + c 26.

∫a
1) 3)

2

dx = sin x + b 2 cos 2 x
2

[EAMCET 2001]

1 ⎛ a tan x ⎞ tan −1 ⎜ ⎟+c ab ⎝ b ⎠
1 ⎛ b tan x ⎞ tan −1 ⎜ ⎟+c ab ⎝ a ⎠

⎛ a tan x ⎞ 2) tan −1 ⎜ ⎟+c ⎝ b ⎠
⎛ b tan x ⎞ 4) tan −1 ⎜ ⎟+c ⎝ a ⎠

Ans: 1 dx sec 2 xdx sec 2 x dx = ⇒∫ 2 Sol: ∫ 2 2 a sin x + b 2 cos 2 x ∫ a 2 sin 2 x sec 2 x + b 2 cos 2 x sec 2 x a tan 2 x + b 2 = 27. 1 ⎛ a tan x ⎞ tan −1 ⎜ ⎟+C ab ⎝ b ⎠
x 2

∫ e (1 − cot x + cot x ) dx =
1) e x cot x + c Ans: 2 2) −e x cot x + c
2

[EAMCET 2000]

3) e x cos ec + c

4) −e x cos ec + c

Sol:

∫ e (1 − cot x + cot x ) dx = ∫ e ( − cot x + cos ecx ) dx
x x 2

Let f ( x ) = − cot x ⇒ f ′ ( x ) = cos ec 2 x ⇒ ∫ e x ⎡f ( x ) + f ′ ( x ) ⎤ dx = e x f ( x ) + c ⎣ ⎦

= −e x cot x + c

Powered by www.myengg.com

Powered by www.myengg.com

Indefinite Integration

28.

sin 6 x ∫ cos8 x dx = 1) tan 7x + c Ans: 2 tan 7 x 2) +c 7 3) tan 7x +c 7

[EAMCET 2000]

4) sec7 x + c

n +1 ⎡ ⎡f ( x ) ⎤ ⎤ sin 6 x tan 7 x n ⎣ ⎦ ⎥ 6 2 Sol: ∫ dx = ∫ tan x sec xdx = + c ⎢∵∫ f ( x ) f ′ ( x ) dx = n +1 ⎥ cos8 x 7 ⎢ ⎣ ⎦

Powered by www.myengg.com